Additively Manufactured Semiflexible Titanium Lattices as Hydrogel Reinforcement for Biomedical Implants. Issue 1 (8th December 2020) - Tosoratti, Enrico; Incaviglia, Ilaria; Liashenko, Oleksii; Leinenbach, Christian; Zenobi-Wong, Marcy
Abstract : Hydrogels are one of the most widespread biomaterials used in tissue engineering. However, they possess weak mechanical properties and are often unstable in load‐bearing applications in vivo. A novel class of flexible Ti–6Al–4V titanium alloy lattices manufactured using laser powder bed fusion (L‐PBF) serves as a tunable reinforcement for hydrogels, providing them with additional mechanical stability and flexibility, while ensuring biocompatibility. A study on the design parameters of the structural elements of the lattices is performed to evaluate their influence on the mechanical properties of the structure. Mechanical testing of Ti–6Al–4V lattices shows a compressive modulus ranging from 38.9 to 895.5 kPa in the flexible direction. In the other two directions, the lattices are designed to have minimal flexibility. Lattices embedded in a 1% agarose hydrogel show a strain‐rate‐dependent, viscoelastic behavior given by the hydrogel component with the additional stiffness of the titanium lattice. Stress distribution upon loading is simulated using finite element analysis (FEA) and compared to experimental data using multiple regression statistical analysis. As a proof of concept, an intervertebral spinal disc implant is designed with mechanical properties matching the compressive moduli of the nucleus pulposus and anulus fibrosus reported in the literature. Abstract : A semiflexible, additively manufactured scaffold for hydrogel reinforcement is designed and manufactured using Ti–6Al–4V powder and laser powder bed fusion. The parametrically designed reinforcement is characterized by means of finite element analysis and compression testing at different strain rates. The method provides a key advancement for reinforcing hydrogels used in tissue engineering.